Radioecological investigations of some Zhytomyr region rivers - E. N. Volkova; V. V. Belyaev; V. G. Klenus; A. Ye. Kaglian; L. P. Yurchuk; V. A. Karapysh (Ядерна фізика та енергетика)
The results of radioecological investigations of ecosystems of Zhytomyr region rivers are given. There are determined 90Sr and 137Cs concentrations in abiotic and biotic components of rivers Gnilopyt’, Irsha and Zherev, situated in the territories with different a density of radioactive pollution. 137Cs concentrations in fishes in river Zherev exceeded two times the admissible levels for that radionuclide.